Mentors, role models, and differences in self-efficacy and motivation among construction management students - Thevenin, Melissa K., author; Elliott, Jonathan, advisor; Lopez del Puerto, Carla, committee member; Gloeckner, Gene, committee member (Colorado State University. Libraries, 2014)
Perceived self-efficacy, motivation, and the presence of mentors and role models have value as predictors of career choice and student success. To understand these constructs within the domain of construction education, a quantitative survey was administered to students enrolled in construction management courses (n = 468) at two large universities. Study results revealed that mean perceived self-efficacy toward construction education was significantly (p < 0.001) higher for construction management (CM) students who report having a role model. Further, CM students who report having a mentor reported a higher mean level of motivation to successfully complete construction education programs and courses (p = 0.015). Differences in self-efficacy and motivation toward construction education between male (n = 410) and female (n = 56) students suggest that female CM students have higher motivation towards construction education (p = 0.024) than their male counterparts. However, due to unequal gender distribution in the sample, coupled with violations of t test assumptions, gender-based findings should be interpreted with caution. This study indicates that students who report having a mentor or role model have higher self-efficacy and motivation toward construction education compared to students without a mentor or role model. The instrument adapted and utilized in the current study can be used to investigate these pertinent construction education-domain specific constructs in order to understand the influence of others on students' academic decisions and performance.
Keywords: motivation; construction education; mentor; role model; self-efficacy; women